2017
DOI: 10.5152/tud.2016.44711
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic donor nephrectomy, complications and management: a single center experience

Abstract: Objective: To present our experience with laparoscopic donor nephrectomy (LDN), our complications and management modalities. Material and methods:Fifty-one transperitoneal LDNs performed in our clinic between the years 2011, and 2015, were evaluated retrospectively. Demographic characteristics of the patients, operative and postoperative data and complications were evaluated.Results: Nineteen female and 32 male patients with ages ranging from 24 to 65 years underwent left-(n=44), and right-sided (n=7) LDNs. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This is the reason why laparoscopic donor nephrectomy is chosen over open surgery [20]. Moreover, in some case series it is reported that the utilization of Gel PortTM (Applied Medical, Rancho Santa Margarita, CA) reduces the warm ischemic time and is of benefit in preventing possible complications during laparoscopy (21).…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why laparoscopic donor nephrectomy is chosen over open surgery [20]. Moreover, in some case series it is reported that the utilization of Gel PortTM (Applied Medical, Rancho Santa Margarita, CA) reduces the warm ischemic time and is of benefit in preventing possible complications during laparoscopy (21).…”
Section: Discussionmentioning
confidence: 99%